Sistem Pendukung Keputusan Pemilihan Kelas Unggulan Dengan Metode Multi Factor Evaluation Process (MFEP) (Studi Kasus : SD Abdi Siswa Bintaro) - Hilarius Tri Nugroho (Jurnal Penelitian Ilmu komputer, 2023)
SD Abdi Siswa Bintaro at Graha Raya Bintaro has held learning activities for 12 years, in November 2016 they had the opportunity to carry out accreditation from the South Tangerang City Education Office and get maximum results with Accreditation A results. special class for outstanding students. The Featured Class was created with the aim of being a role model for other students. This Decision Support System was built with a WEB-based application using the PHP programming language and using a MySQL database and the method used is the Multifactor Evaluation Process. The determination is clearer and the resulting decisions for the Preferred Class are more accurate because they are in accordance with the existing facts/reality. The settlement method used in this study is by processing data which is the output in the form of constants or linear equations. The Multifactor Evaluation Process method is a method in which MySQL writes down the factors and calculation criteria in the form of weight values from 0 to 5. In the assessment process for prospective 4th grade students to enter the superior class, they still use the manual method. This developed system can assist the assessment process with a computerized system.